ISOLASI DAN UJI AKTIVITAS ANTIFUNGI EKSTRAK ETANOL KULIT BUAH DELIMA MERAH (Punica granatum L.) TERHADAP Candida albicans - More, Evanisia; Mbulang, Yohana; Krisyanti, Yulia (Jurnal Farmasi & Sains Indonesia, 2023)
The research about isolation and antifungal activity test of ethanol extract of Punica granatum L peel towards Candida albicans’ has been done. The objectives of this study are to determine any secondary metabolite compounds that can be isolated from Punica granatum L peel, to determine antifungal activity of Punica granatum L peel extract and to determine the most effective concentration to inhibit Candida albicans’ growth. Based on phytochemical test result, it can be concluded that secondary metabolite compounds contained in Punica granatum L peel extract are flavonoide and tannin. The process was continued by TLC and PTLC. Based on TLC process, eluent with best separation was methanol:ethyl acetate (3:1) with 0,44 and 0,51 as the Rf values. The eluent from the following TLC was used for PTLC process. PTLC results showed one round spots, the yellow one with Rf value = 0,77. The following process was antifungal activity test using agar diffusion method and Candida albicans was used for this purpose. The antifungal testing process was done by varying the concentration of Punica granatum L peel extract to 10%, 20%, 40% and 50%. The result showed that the four concentrations can inhibit the Candida albicans’ growth, indicated by transparent zone surrounding the concentration. One way Anova results Fcount> Ftable = 116,709727> 5,064, it indicates that there is significant influence of various concentration to resistivity zone diameter. The process continued by analyzing the most effective concentration using multiple Tukey comparative test with 1% significance level. The result showed that the most effective concentration to inhibit Candida albicans’ growth was 50% Punica granatum L peel extract with its resistivity capacity is 22,26 mm.